DESIGN THINKING IN MATHEMATICS EDUCATION FOR PRIMARY SCHOOL: A SYSTEMATIC LITERATURE REVIEW - Muhammad Zaim George Man; Riyan Hidayat; Mohamad Khairuzzamir Kashmir; Nurul Fatihah Suhaimi; Mashitah Adnan; Azizah Saswandila (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2022)
Design Thinking is a knowledge as a thriving innovation practice and an approach to creative problem solving. The main purpose of this study is to review existing studies which are related to the Design Thinking in Mathematics Education for primary school. The search terms were used by inserting the suitable keywords based on the main topic such as "design thinking", "mathematics education", "mathematics", "primary school" and "elementary school". Systematic Literature Review (SLR) was conducted to gain information for better understanding regarding our topic. This SLR was performed through two search engines which were SpringerLink and Scopus. In reporting this study, the PRISMA guidelines were followed. We identified and screened 1123 articles published between 2017 until 2021 in SpringerLink and Scopus. After elimination of duplicates and non-relevant topics, there were 23 articles remained based on the inclusion and exclusion criteria. The limited number of studies on the main topic as design thinking for primary school caused the small numbers of articles were selected. This is because there are many articles about teachers and post-graduate. Our findings indicated that the year of 2021 was mostly research conducted, followed by the year of 2020, 2019 and 2017 meanwhile there is no research conducted in 2018. Concerning the geographical distribution of the authors, the findings indicated that the predominant authors that developing the design thinking were in Germany, Australia, USA, Singapore and Switzerland, and only a few research conducted in Hong Kong, Sweden, Cyprus, Israel, Turkey, UK, Spain, Canada, Netherlands, Malaysia, and mixed countries. From the results, we can see that this design thinking should be practiced by teachers in their teaching regardless of whether it is mathematics or any other subject. In conclusion, design thinking among the students, especially primary school students nowadays, is indispensable to ensure that our country is always moving forward in the era of globalization.